2018
DOI: 10.25174/2249-4065/2018/79291
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics of wheat rhizosphere for abiotic stress management

Abstract: Plant microbiome also known as it's second or extended genome, regulates and influences plant's metabolism and growth. The plant microbiome members promote nutrient uptake, tolerance against abiotic and biotic stresses and regulate host immune system. Although there is plenty of information available on role of rhizosphere microbiome for plant growth, but still there is dearth of knowledge for the vast majority of rhizosphere microorganisms. This is mainly due to their unknown growth requirements or inability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The evolution of bacterial communities in rhizospheric samples from wheat fields was studied by Donn et al (2015). Ahlawat et al (2018) deduced the eventual significance of rhizospheric bacteria to combat stress conditions by studying the metagenomics of wheat rhizosphere. Germida and Siciliano (2001) have shown that the taxonomic diversity of bacteria congregated to the roots of modern, recent, and ancient cultivars of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of bacterial communities in rhizospheric samples from wheat fields was studied by Donn et al (2015). Ahlawat et al (2018) deduced the eventual significance of rhizospheric bacteria to combat stress conditions by studying the metagenomics of wheat rhizosphere. Germida and Siciliano (2001) have shown that the taxonomic diversity of bacteria congregated to the roots of modern, recent, and ancient cultivars of wheat.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible to culture only very limited numbers of microorganisms and analysis of them for beneficial traits by using cultural methodology. However, techniques like metagenomics are very tough in analytical study of whole community interaction and coordination between different components of the community and metabolic pathways or genes activity under particular to relevant environmental condition with own specificity [20] [21].…”
Section: Discussionmentioning
confidence: 99%
“… Zolla et al (2013) , work on drought stress conditions in Arabidopsis thaliana using the pyrosequencing approach reported the robust set of soil microbes having an ability to sense abiotic stress and increase plant biomass production along with reduced expression of drought response marker genes ( Zolla et al, 2013 ). A similar study on wheat rhizosphere for abiotic stress management reported the wider and diversified role of metagenomics in ASM where metagenomics of wheat along with its application in climate-resilient genotypes development is elaborated ( Ahlawat et al, 2018 ).…”
Section: Metagenomics and Sustainable Agriculturementioning
confidence: 99%